Motivation of Human Talent and Its Relationship with Citizen Service in a Local Government in Lima, Peru, 2017 - Calle Terrones, María Patricia (2022)
This research aimed to establish the relationship between motivation of human talent and citizen service. From a population of 3192 local government workers, a sample of 343 at 95% confidence level was obtained. A Likert-type scale survey was used for data collection. Based on the results, variables “motivation of human talent” and “customer service” are positively correlated (0.57). The dimensions of variable “motivation of human talent” are: “intrinsic motivation” and “extrinsic motivation”; the dimension of variable “citizen service” is “service provided by the staff”. It is concluded that the motivation of human talent is related to citizen service.